2022
DOI: 10.5713/ab.22.0142
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of broiler chickens fed reduced-energy diets supplemented with emulsifiers

Abstract: Objective: To investigate the physiological effects of exogenous emulsifiers in broiler chickens that were fed tallow-incorporated reduced-energy diets over 35 days.Methods: A total of 256 Ross 308 one-day-old broilers (42.28 ± 0.16 g) were randomly allocated in a 2 × 2 factorial arrangement to 32 pens with eight chicks per cage. Birds were fed one of four dietary treatments as follows: (1) positive control (PCN; energy sufficient diet); (2) negative control (NCN; energy-deficient diet, -100 ME kcal/kg); (3) P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In addition, the ME levels × emulsifier interaction effect in BWG and improved FCR by emulsifier supplementation during d 28 to 42 indicate that the emulsifier has beneficial effects on the BWG of birds fed reduced ME diets. In agreement with our result, other studies reported that using single or blended emulsifiers containing sodium stearoyl lactylate, glycerol monostearate, and glyceryl distearate improved BWG and FCR of broiler during the finisher and overall period ( Wang et al, 2020 ; Hoque et al, 2022 ; Oketch et al, 2022 ). In addition, many studies have confirmed that exogenous emulsifiers positively affect key growth performance parameters ( Jansen et al, 2015 ; Chen et al, 2019 ; Ge et al, 2019 ), suggesting that emulsifiers are indeed cost-effective feed additives to improve nutrient utilization and growth performance in broilers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the ME levels × emulsifier interaction effect in BWG and improved FCR by emulsifier supplementation during d 28 to 42 indicate that the emulsifier has beneficial effects on the BWG of birds fed reduced ME diets. In agreement with our result, other studies reported that using single or blended emulsifiers containing sodium stearoyl lactylate, glycerol monostearate, and glyceryl distearate improved BWG and FCR of broiler during the finisher and overall period ( Wang et al, 2020 ; Hoque et al, 2022 ; Oketch et al, 2022 ). In addition, many studies have confirmed that exogenous emulsifiers positively affect key growth performance parameters ( Jansen et al, 2015 ; Chen et al, 2019 ; Ge et al, 2019 ), suggesting that emulsifiers are indeed cost-effective feed additives to improve nutrient utilization and growth performance in broilers.…”
Section: Discussionsupporting
confidence: 93%
“… Hoque et al (2022) reported that sodium stearoyl-2-Lactylate supplementation levels linearly improved FCR in broilers fed reduced ME diets during d 1 to 7 and d 7 to 21. Oketch et al (2022) revealed that the blended emulsifier containing sodium stearoyl lactylate, glycerol monostearate, and glyceryl distearate improved the FCR during d 0 to 28. In addition, similar studies also found that exogenous emulsifier supplementation improved growth performance during the starter and grower periods ( Khonyoung et al, 2015 ; Ge et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Such improvements could translate to enhanced intestinal absorption activity. Marginal improvements in the villus absorptive surface area have also been reported (Oketch et al, 2022). The morphological improvements could result from the synergistic interactions of feed ingredients including dietary emulsifiers as opposed to the influence of the emulsifier in isolation (Brautigan et al, 2017).…”
Section: Ileal Histomorphology and Gut Healthmentioning
confidence: 86%
“…Figure 1 summarises the nutritional, biochemical, and physiological roles of dietary lipids in animals. However, there is a physiological age‐related depression in the capacity of young birds to utilise dietary lipids effectively (Oketch et al, 2022). Therefore, several strategies toward optimising the energy‐yielding potential of dietary lipids including the supplementation of exogenous emulsifiers have been investigated (Ravindran et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The head and the shanks were then separated at the first cervical vertebra and the ankle joint, respectively [32]. The birds were then weighed, and the resulting value was recorded as the hot carcass weight [33]. The carcass percentage was then calculated using the hot carcass weight as a percentage of the live body weight.…”
Section: Carcass Evaluationmentioning
confidence: 99%